TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) INSTRUMENT FOR INDONESIA SCIENCE PRE-SERVICE TEACHER: FRAMEWORK, INDICATORS, AND ITEMS DEVELOPMENT - Hidayat, Arif (Unnes Science Education Journal, 2019)
Teacher education program design using Shulman’s Pedagogical Content Knowledge (PCK) is inadequate informing the professional capabilities of a future teachers to deal with technology integration to enhance teaching and learning in the 21st century. Adding Technology as another core component and its relationship to being Technological Pedagogical Content Knowledge (TPACK) by Mishra and Koehler (2005) is wide. The paper presents the case that preparing the instrument to measure TPACK for pre-service science teachers is one of the important aspects. The research aimed to define indicators and items development of the TPACK instrument for Indonesia's pre-service science teacher. Seven sub-domain indicators i.e.: Content Knowledge (CK), Pedagogy Knowledge (PK), Technology Knowledge (TK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), TPACK itself, and items are developed according to its rational. The paper discusses the rationale and its background on 31 indicators with 116 items resulted from this research and seeking for further validation and other necessary statistical processes